Traumatic Bilateral Pneumothoraces due to Sternal Wire Migration - Umar Imran Hamid; Scott Gillespie; Colum Lynchehaun; Haralabos Parissis (Case Reports in Medicine)
Sternal wound complications after cardiac surgery are associated with increased morbidity and mortality. Wire migrations associated with sternal dehiscence can lead to catastrophic haemorrhage unless intervened in time. We present a case of sternal wire migration causing bilateral pneumothoraces.